2008
DOI: 10.1016/j.jada.2007.10.034
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Related Hypoferremia Is Not Explained by Differences in Reported Intake of Heme and Nonheme Iron or Intake of Dietary Factors that Can Affect Iron Absorption

Abstract: Hypoferremia is more prevalent in obese than nonobese adults, but the reason for this phenomenon is unknown. To elucidate the role dietary factors play in obesity-related hypoferremia, the intake of heme and nonheme iron and the intake of other dietary factors known to affect iron absorption were compared cross-sectionally from April 2002 to December 2003 in a convenience sample of 207 obese and 177 nonobese adults. Subjects completed 7-day food records, underwent phlebotomy for serum iron measurement, and had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
100
5
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 17 publications
13
100
5
5
Order By: Relevance
“…It is stated that increased body fat, especially visceral fat, predisposes towards worse iron homeostasis due to an increased rate of pro-inflammatory cytokines produced by visceral adipose tissue [20][21][22][23][24][25]. A large-scale study conducted on obese patients revealed also a positive correlation between TIBC and the percentage content of fat tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is stated that increased body fat, especially visceral fat, predisposes towards worse iron homeostasis due to an increased rate of pro-inflammatory cytokines produced by visceral adipose tissue [20][21][22][23][24][25]. A large-scale study conducted on obese patients revealed also a positive correlation between TIBC and the percentage content of fat tissue.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Menzie et al revealed that dietary iron intake and its estimated bioavailability are similar in obese and normal weight subjects [22,24]. On the other hand, an increased level of proinflammatory cytokines, adipokines and hepcidin, may impair iron absorption [22].…”
Section: Discussionmentioning
confidence: 99%
“…9,[14][15][16] It has also been suggested that reduced iron intake due to poor dietary choices by overweight individuals may contribute to poor iron status, but there is little data to support this. 1,9,15,16 In adults, dietary iron intake and its estimated bioavailability are similar in overweight and normal weight adults, 17 but no data are available for children. Even if iron intakes and estimated dietary bioavailability are similar, absorption of dietary iron could be reduced in overweight individuals if the circulating hepcidin level is increased.…”
Section: Introductionmentioning
confidence: 99%
“…Учитывая наличие явных про-тиворечий по поводу связи гипоферремии при ожирении и алиментарного дефицита железа (Hassapidou et al, 2006;Menzie et al, 2008), вклад данной причины в генез гипоферремии остается дискуссионным. Что касается увеличения объема циркулирующей крови у индивидуумов с ожире-нием, данное предположение было подтверждено в эксперименте (Bertinato et al, 2013).…”
Section: железо как потерпевшийunclassified